A Bibliometric Analysis of Virtual Influencer - Muslimah, Dinda Desmonda; Sunengsih, Ayu (West Science Interdisciplinary Studies, 2023)
In the current digital era, Virtual Influencers have become a trending phenomenon in social media. This research utilizes bibliometric analysis to explore the developments in Virtual Influencer-related studies, with a focus on the involvement of Artificial Intelligence (AI) technology in their creation. The study also identifies the most influential works, active researchers, and journals at the forefront of publication. Additionally, it unveils the evolution of the concept of virtual influencers from an AI perspective. The research aims to analyze how AI influences marketing strategies through virtual influencers, enabling the optimization of AI-based virtual influencer usage in creating authentic and relevant experiences for today's digital consumers. This study enhances our understanding of AI's role in shaping the future of influencer marketing and opens opportunities for further innovation in virtual influencer research. The research also provides insights into virtual influencers and their role in shaping social media trends and consumer culture transformation in the digital era.